RETRACTED: Water quality analysis in the system of rational use of natural resources (using the example of the Rostov region) - Ovchinnikova Natalia; Sharkova Marina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001